Outcome of expectant line of management in early onset (24-32weeks) pregnancy induced hypertension - Mandade, Krishna; Singh, Kashika; Bhavthankar, D. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is a disease of multiple organ systems that is unique to pregnancy and is often associated with increased risk of maternal-perinatal adverse outcome, especially when it is severe and occurs well before term. The objective of the study was to study expectant line of management in early onset pregnancy induced hypertension (24-32 weeks) and its maternal and perinatal outcome in relation to preterm delivery, IUD/ Still birth, and early neonatal deaths. Methods: Total 100 patients presented with early onset pregnancy induced hypertension admitted in Pravara Medical College and Hospital. 50 patient’s pregnancy terminated (Aggressive Group) depending on patients clinical profile and other 50 patients given expectant line of management and pregnancy was prolonged (Expectant Group). Maternal and perinatal outcome was compared between the two groups. Results: No maternal mortality was seen in both groups. Perinatal mortality in aggressive line of management was 54% while in expectant line of management perinatal mortality was 30%. Neonatal deaths account for 24% in aggressive group and 10% in expectant group. Fetal survival rate in expectant group was 70% and in aggressive group it was 46%. Conclusions: Expectant management of severe preeclampsia at 24 to 32 weeks in a tertiary care center is associated with good perinatal outcome with a minimal risk for the mother. The early use of antihypertensive drugs, optimum timing of delivery and strict fluid balance will help to achieve successful outcome.